Trade and Investment Relations Between India and Bangladesh: Status and Possibilities. - Ghuman, Ranjit Singh and Madaan, Davinder Kumar (2011)
Trade and Investment relations between neighbouring countries, like India and Bangladesh, are a natural phenomenon. Before independence, the two countries were part of India and there was a great-amount of inter-regional economic interference on each other. After Independence in 1947, Bangladesh (then East Pakistan) became part of Pakistan. It became a separate country in 1972 and came to be known as Bangladesh. Both the countries are founder members of South Asian Association for Regional Cooperation (SAARC) which has now attained the status of SAFTA (South Asian Free Trade Association). This paper has tried to discuss the present status of trade and investment relations between India and Bangladesh since 1975. Though their mutual trade has been increasing since 1975, yet, it could not exploit the latent trade potentialities. The balance of trade has been heavily in favour of India. The limited export capacity of Bangladesh, inter alia, seems to be one of the important reasons behind it. The joint ventures in investment and trading can address this issue. They can reap great amount of gains by expanding their mutual trade and undertaking joint investment in each other‘s territory. The data reveals that both the countries have been benefitting from their mutual trade, though in a limited manner, in the past. Both the countries need to explore the possibilities of expanding their trade and investment and thereby strengthening their mutual economic relations. India, being a large economy, needs to, shoulder greater responsibility in this direction as investment component is nearly non-existant. The resolution of some long-standing irritants is also very important to move forward in attaining higher stages of economic cooperation. The cordial political relations between the two countries would not only enhance their trade and investment but also help them to concentrate on other pressing problems, such as, illiteracy, poverty, unemployment, environment and under-development